1998
DOI: 10.1021/ma971108a
|View full text |Cite
|
Sign up to set email alerts
|

Phase Equilibria of Lattice Polymers from Histogram Reweighting Monte Carlo Simulations

Abstract: Histogram-reweighting Monte Carlo simulations were used to obtain polymer / solvent phase diagrams for lattice homopolymers of chain lengths up to r=1000 monomers.The simulation technique was based on performing a series of grand canonical Monte Carlo calculations for a small number of state points and combining the results to obtain the phase behavior of a system over a range of temperatures and densities. Critical parameters were determined from mixed-field finite-size scaling concepts by matching the order … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
165
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 166 publications
(190 citation statements)
references
References 21 publications
25
165
0
Order By: Relevance
“…Both are in good agreement with previously reported values. 4,6 The high linearities in the figure confirm that x 3 ϭ0.5. Figure 4 shows a log-log plot of critical compositions as a function of chain length.…”
Section: Resultsmentioning
confidence: 52%
See 2 more Smart Citations
“…Both are in good agreement with previously reported values. 4,6 The high linearities in the figure confirm that x 3 ϭ0.5. Figure 4 shows a log-log plot of critical compositions as a function of chain length.…”
Section: Resultsmentioning
confidence: 52%
“…Experimental data 1 show that x 2 ϭ0.38Ϯ0.01. Recent simulation results [4][5][6] for reasonably long chains also give x 2 ϭ0.38Ϯ0.01; earlier simulation data gave much lower values for x 2 , but the chain lengths involved in those simulations were not long enough to be in the scaling regime. [7][8][9][10][11] Equation ͑3͒ describes the scaling behavior of the critical temperature as a function of chain length.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Polymer phase coexistence curves have been published for significantly longer chain lengths ͑up to 1000͒ using lattice models, 24,25,27 that were simulated using the Gibbs ensemble and grand-canonical ensemble methodologies. In a lattice model a solvent molecule can simply be represented as an empty lattice site.…”
Section: Discussionmentioning
confidence: 99%
“…Wilding et al 25 found xϭ0.37 and Yan et al 26 reported that xϭ0.27. Finally, Panagiotopoulos et al 27 found a value x ϭ0.38. Our exponent clearly falls within the range of values found in the lattice simulations.…”
Section: ͑20͒mentioning
confidence: 96%